2014
DOI: 10.1136/gutjnl-2014-307150
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucus affinity and biological activity of an orally administered antibacterial and anti-inflammatory peptide

Abstract: Our findings demonstrate the anti-inflammatory activity and mucus affinity of the synthetic AMP Pep19-2.5 and characterise the influence on microbiota composition and enteropathogen infection after oral administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 53 publications
(49 reference statements)
0
34
1
Order By: Relevance
“…peptide-mucin interaction does not affect peptide activity and is reversible. 2,13 In accordance, cryptdin-coated bacteria were visualized within the mucus layer.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…peptide-mucin interaction does not affect peptide activity and is reversible. 2,13 In accordance, cryptdin-coated bacteria were visualized within the mucus layer.…”
mentioning
confidence: 78%
“…Despite these technical obstacles, a number of studies during the past decade have revealed the synthesis and structural organization of the mucus matrix and its critical role during homeostasis and antimicrobial host defense. [1][2][3] Using the mucus preserving Carnoy fixative, Matsuo et al and Swidsinski et al demonstrated the existence of a bacteria-free zone separating the enteric epithelium from the microbiota. [4][5] Later, Johansson et al showed the presence of bacteria within the outer, but not the inner, colonic mucus layer consistent with the finding that mucus represents an important nutrient source of enteric commensals.…”
mentioning
confidence: 99%
See 3 more Smart Citations